URGENSI PEMBUATAN MODEL PREDIKTIF DALAM TATA KELOLA BISNIS - Abdul Rahman (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Predictive modeling is a mathematical and statistical method for predicting future behavior or trends by analyzing input data patterns. This is part of predictive analysis using current and historical data to predict or estimate future events. This paper aims to examine the importance of predictive modeling in business affairs. The method used in this paper is literature review. Data was collected by conducting literature searches, both books and journals. The results of the study show that predictive analytics is an organizational game changer that aims to improve the competency retrieval process and increase efficiency. By leveraging large amounts of data, predictive analytics allows businesses to predict future outcomes by analyzing historical data, identifying trends, and creating insights that can be implemented in the field. For business analysts, understanding predictive analytics is critical to establishing data-driven strategies and addressing the ethical considerations that accompany data manipulation.